Pembatalan Perkawinan Akibat Pemalsuan Identitas Pengadilan Agama Bandung - Kamelia, Kamelia; Husna, Veny Nisratul; Pranata, Ardian Ari; Hikmah, Lisda Jumatul; Armasito, Armasito (Berasan: Journal of Islamic Civil Law, 2024)
This study aims to analyze the factors that cause the annulment of marriage due to identity forgery, the evidentiary process at the Bandung Religious Court, and the legal consequences for related parties. This research is an empirical research. Empirical legal research aims to obtain data and information on the practice of marriage annulment due to identity forgery at the Bandung Religious Court. The data and information that can be collected in this study include court decisions related to the annulment of marriage due to identity forgery. The annulment of marriage is carried out after the marriage has been completed, but also by using the same reason as the reason for the prevention of marriage. Based on the results of the research, it was concluded that the annulment of marriage due to identity forgery at the Bandung Religious Court was caused by several factors, such as the desire to get benefits, dishonesty, and administrative errors. The evidentiary process in this marriage annulment case requires strict proof and is based on valid evidence. Legal consequences for parties who falsify identity can be in the form of annulment of marriage, return of property, and liability for wedding expenses.